Analysis of the Satisfaction of Nursing Students towards E-learning of the Medical-Surgical Nursing Subject during Pandemic - Putu inge ruth suantika; Yustina Ni Putu Yusniawati (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: The whole world is dealing with the covid-19 pandemic. Therefore, the government has taken a policy to transform the education system from in-class to remote learning. Nursing students are adapting to this system, maintaining learning activities through unfamiliar online methods. One of the subjects they take during this pandemic is Medical-Surgical Nursing. This online learning system has created new challenges in the teaching-learning process on the Medical-Surgical Nursing subject. Students tend to feel disinterested, which leads to a sense of dissatisfaction during online learning. Purpose: This study aimed to analyse the satisfaction of nursing students towards e-learning of the Medical-Surgical Nursing subject during the pandemic. Methods: This research used descriptive analysis with a cross-sectional research design and used a self-administered questionnaire. The samples of 300 respondents were nursing students at private and public universities in Denpasar. The research started from January to July 2021 from proposal making to data processing This study used univariate and bivariate analysis involving the logistic regression test. Results: There is a relationship between the variables of accessibility, understanding the material, interactivity, and method accuracy. The regression equation is -5.336 + 0.011 for Accessibility, + 0.474 for Material, + 0.021 for Interactivity, + 0.150 for Utility, and - 0.093 for Self-Reliance. Conclusion: The conclusion in this research is that the convenience of obtaining materials is the most significant relationship.